Distributed, ambient, and pervasive interactions : 4th International Conference, DAPI 2016, held as a part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016, proceedings /: 4th International Conference, DAPI 2016, held as a part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016, proceedings. ([2016]) - Unknown
No abstract available